LGBT-Parent Families
XV, 371 p. 2 illus. in color.
Keywords: “This first-rate handbook provides a comprehensive, astute, and accessible view of LGBT-parent families. With contributions from an interdisciplinary and international group of leading scholars, this volume covers every contemporary topic concerning LGBT families, including transgender parenting and LGBTQ youth with LGBTQ parents. Co-editors Drs. Goldberg and Allen have done an outstanding job in assembling experts to present overviews of the research and suggest applications for clinical work, policy, and advocacy. I highly recommend that this book be included in college and post-graduate social science courses on family life. This manual is essential reading for all clinicians.” - Nanette Gartrell, MD, Williams Institute Visiting Distinguished Scholar, UCLA School of Law, Principal Investigator, U.S. National Longitudinal Lesbian Family Study “The appearance of a handbook on LGBT-parent families signals and advances the mainstreaming of a category of family that just a short time ago was utterly marginal, subversive, even illegal.”—from the Foreword by Judith Stacey, Ph.D. Paralleling their gains in legal rights and social acceptance is a rapidly growing knowledge base concerning sexually diverse families. Emphasizing what we know and what we still need to know about this maturing field, LGBT-Parent Families covers both major and less-studied areas of research, exploring clinical, methodological, policy, and advocacy issues alongside the contexts in which parents practice their craft and children experience their world. Inclusiveness beyond sexuality and gender is a crucial dimension of this volume: issues of race/ethnicity, social class, and geographic diversity are discussed by most of the contributors, including a chapter devoted to non-Western perspectives. Diverse, too, are the disciplines represented in the book, from psychology and psychiatry to human development and legal studies. Among the topicscovered: Lesbian and gay adoptive parents A call for research on bisexual parenting Transgender-parent families LGBTQ youth with LGBTQ parents Lesbian, gay, bisexual, and transgender grandparents Clinical work with LGBTQ parents and prospective parents Qualitative research on LGBT-parent families Use of representative datasets to study LGBT-parent families Use of multilevel modeling to study LGBT-parent families Geared toward researchers in family relations, family sociology, and public health as well as to policymakers and clinicians, LGBT-Parent Families breaks progressive new ground with an eye toward an egalitarian future.